The effect of COVID-19 pandemic on diabetes care indices in Southern Iran: an interrupted time series analysis - Alireza Mirahmadizadeh; Mohammad Hossein Sharifi; Jafar Hassanzadeh; Alireza Heiran; Fariba Moradi Ardekani; Neda Hadizadeh; Mehdi Sharafi; Mohammad Mohammadi Abnavi (BMC, 2023)
Abstract Background Type 2 diabetes mellitus (T2DM) requires a continues bulk of cares. It is very probable COVID-19 pandemic is affected its healthcare coverage. Methods The interrupted time series analysis is used to model the trend of diabetes healthcare indices, such as the health worker visits, physician visits, body mass index (MBI), fasting blood sugar (FBS), and hemoglobin A1c (HbA1c), before and after the start of COVID-19 pandemic. The reference of data was the totals of all T2DM patients living in Fars Province, Southern Iran, areas covered by Shiraz University of Medical Science (SUMS), from 2019 to 2020. Results A significant decrease for visits by the health workers, and physicians was observed by starting COVID-19 pandemic (β2 = -0.808, P < 0.001, β2 = -0.560, P < 0.001); Nevertheless, the coverage of these services statistically increased by next months (β3 = 0.112, P < 0.001, β3 = 0.053, P < 0.001). A same pattern was observed for the number of BMI, FBS and HbA1c assessments, and number of refer to hospital emergency wards (β3 = 0.105, P < 0.001; β3 = 0.076, P < 0.001; β3 = 0.022, P < 0.001; β3 = 0.106, P < 0.001). The proportion of T2DM patients with HbA1C < 7%, and controlled hypertension during study period was statistically unchanged. Conclusions When the COVID-19 pandemic was announced, T2DM healthcare coverage drastically decreased, but it quickly began to rebound. The health monitoring system could not have any noticeable effects on diabetes outcomes.